Making new franchise systems work - Shane, Scott A. (Strategic Management Journal, 1998)
This paper argues that new franchise systems are more likely to survive if they are structured to economize on agency costs. After controlling for industry effects, and firm age and size, this paper shows empirical support for six of nine hypotheses about the linkage between mechanisms for economizing on agency costs and the survival of new franchise systems. © 1998 by John Wiley & Sons, Ltd.